The Antimicrobial Effects of Ethanolic and Methanolic Extracts of Rhubarb on Listeria monocytogenes and Yersinia enterocolitica - Mohammad Ali Fotouhi Lasibi; Hamdollah Moshtaghi (Trends in Pharmaceutical Sciences, 2023)
Objective(s): The harmful effects of antibiotic misuse have been demonstrated as a cause of the spread of antibiotic-resistant pathogens. Due to the increasing resistance of bacteria to antibiotics, there is a need to use new substances to control bacteria. Recently, there has been an interest in identifying plants with pharmacological and antibiotic effects. Materials and methods: This study was performed to evaluate the antibacterial effects of Iranian rhubarb (Rheum ribes) in vitro on Listeria monocytogenes and Yersinia enterocolitica. For this purpose, ethanolic and methanolic extracts of roots, stems, leaves, and flowers of rhubarb were prepared, and the antibacterial effects of the extracts were evaluated by the broth microdilution method. Results: The results showed the antimicrobial effect of methanolic extracts of different parts of the rhubarb plant is more than its ethanolic extracts and the effect of rhubarb extract on L. monocytogenes is more than its effect on Y. enterocolitica. The most antimicrobial effect on L. monocytogenes belongs to the methanolic extracts of leaves and stems, and the ethanolic extracts of leaves, and stems. Concerning Y. enterocolitica, the most antimicrobial properties belong to the methanolic extracts of leaves and ethanolic extracts of stems. Conclusions: Among the ethanolic and methanolic extracts of different parts of rhubarb, the most antimicrobial effect belongs to the methanolic extract of the leaf and the ethanolic extract of the stem. Herbal extracts can be investigated for their beneficial effects in the control of foodborne infectious diseases.